Effect of Helichrysum italicum on the electrochemical corrosion behaviour of iron in simulated acid rain solution - Pilić, Zora (Array, 2019)
The aqueous extract of the Helichrysum italicum leaves (HI) is tested as a corrosion inhibitor of an iron in a simulated acid rain using potentiodynamic polarisation, cyclic voltammetry and electrochemical impedance spectroscopy. Results of all electrochemical methods indicate an increase of a corrosion inhibition efficiency of the iron with the HI extract concentration. Maximum inhibition efficiency (~ 50 %) is obtained at 2.0 g L–1 HI extract. The inhibitive action is assumed to occur via an adsorption of the HI extract on the iron surface. Results indicate that the adsorption process is spontaneous and follows the Freundlich adsorption isotherm. According to the calculated ΔG value (~ 15 kJ mol–1), the corrosion inhibition of the iron occurs predominantly via a physisorption of the HI extract. The concentration of iron ions released into a solution, measured by atomic absorption spectrometry, is in accordance with the electrochemical results.